The Mechanism for Estimating the Percentage of Illicit Gains in Financial Disclosure Declarations and Its Effectiveness in Protecting Public Funds: A Comparative Study - lbrahim, Rabab (Journal of Legal Sciences, 2025)
This research aims to demonstrate the impact of the mechanism for estimating the percentage of illicit gains in financial disclosure declarations on its effectiveness in protecting public funds. An effective mechanism must be established to fulfill its primary purpose — safeguarding state assets. To identify the optimal mechanism for achieving this objective, the study adopts an analytical approach to the legislative texts related to this subject in Iraq, in order to identify areas of weakness and deficiency. Additionally, a comparative approach is employed by examining the corresponding legislation in Egypt and Jordan. Specifically, the study compares Iraq’s Federal Commission of Integrity and Illicit Gains Law No. 30 of 2011 (as amended) with the relevant laws in Egyptian and Jordanian legislation.